Pendampingan Optimalisasi Media Sosial Sebagai Sarana Pemasaran Produk - Raharjo, Taufik; Prasetyo, Dhedy Hendro (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
The purpose of this study is to provide knowledge and skills in the optimization of social media as a means of product marketing for Tsaqofi Community. This activity has been done with the e-learning method through the utilization of the WhatsApp group. This activity was held for a month involving nine participants. After participating in this activity, participants have understood the benefit of social media to develop their business. Participants also have practiced the theory given, so that they felt the positive advantage of community service activities.